Playful strategy for teaching themes: reproductive organ, contraceptive and sexually transmitted methods in high school in Santarém-Pará (Research, Society and Development, 2022)
Playfulness is capable of providing, in the school environment, a space for integration, which encourages the student to be more participatory, encouraging him to build his knowledge. In this context, the present work aimed to identify the contributions of the game "Corrida dos spermatozoides" associated with expository classes for the teaching of biology to students of the second year of high school. The project was developed in the public school of education in the city of Santarém-PA. In 2nd grade high school classes. Playful strategies were worked with expository samples and games. Initially, a pre-test was applied containing ten objective questions, in order to verify the students' prior knowledge on the subject, after the playfulness a post-test was applied. It was observed through the applications of the project, that the use of playful strategies provided a space for interaction, motivation and creativity, enabling the construction of knowledge in a collective way and establishing ways to explore other spaces, transforming the classroom into a place of generation of knowledge.